Practical Solutions to Address COVID-19-Related Mental and Physical Health Challenges Among Low-Income Older Adults - Bergeron, Caroline D.; Boolani, Ali; Jansen, Erica C.; Smith, Matthew Lee (Frontiers in Public Health, 2021)
Low-income older adults are disproportionately impacted by the COVID-19 pandemic. In this perspective article, we review the context in which low-income older people experience the pandemic and the mental and physical health consequences they have faced to date. Then, we offer practical solutions to help improve low-income older adults' sleep, physical activity, nutrition, and stress that require no or low financial commitment. We argue that governments, communities, and organizations should make greater efforts to promote healthy living for low-income older adults in times of health emergencies to ensure their ability to be universally adopted, regardless of income and resources.